Traceable ring signature scheme based on domestic cryptographic algorithm SM9 - XIE Zhenjie; YIN Xiaokang; CAI Ruijie; ZHANG Yao (Tongxin xuebao)
To address the privacy protection issues of digital signature users and prevent the misuse of complete anonymity by malicious users, a traceable ring signature scheme based on the domestic cryptographic algorithm SM9 was proposed. The SM9 algorithm was an identity-based cryptographic algorithm independently developed by China, which was characterized by high security and excellent performance, eliminating the costs associated with public key infrastructure construction and certificate management. By introducing a cryptographic accumulator, the computational costs of ring signature generation and verification, as well as the size of the signature data, were reduced to a constant level. Under the random oracle model, the scheme was proven to achieve EUF-CMIA security based on the q-SDH hard problem, and it was demonstrated to have conditional anonymity, enabling the tracing of the actual signer in case of disputes. Theoretical analysis and experimental results show that the signature and verification efficiencies of the proposed scheme are 7.3 times and 3.3 times, respectively, higher than those of existing similar schemes, while the signature data size was approximately one-fifth of theirs. This scheme exhibits significant advantages in both computational efficiency and communication overhead.